Debut of gastric cancer with brain metastasis: clinical surgical management - Romero Ayala, Javier (2022)
Gastric cancer is one of the most frequent worldwide. Brain metastases from gastric cancer are rare and are diagnosed in less than 1% of patients with gastric cancer. We present the case of a 61-year-old woman with a history of decreased visual acuity, headache, and involuntary movements. She underwent an MRI that showed a left occipital extraparenchymal appearance lesion. The PET scan reveals a hypermetabolic zone in the lesser curvature of the stomach, and the endoscopy reveals a lesion suggestive of gastric malignant neoplasia in the Borrmann I fundus. It was decided to perform a tumor excision by neurosurgery, whose pathological anatomy study revealed metastatic adenocarcinoma to the brain. She undergoes a total D2 gastrectomy, no other metastases are evident. The patient evolves favorably in the postoperative period. The pathology study revealed a poorly differentiated adenocarcinoma. In Peru and in the world, standard recommendations on how to treat these patients have not yet been established, although it is known that surgical resection of brain metastases can significantly decrease morbidity and prolong survival compared to non-surgical approaches. As far as we know, it is the first report of this type presented in the country.